Interleaved CSC converter‐based power factor corrected switched mode power supply for arc welding. Issue 12 (1st October 2016) - Narula, Swati; Singh, Bhim; Bhuvaneshwari, Gurumoorthy
Abstract : This paper focuses on the design and development of power factor corrected (PFC) interleaved canonical switching cell (I‐CSC) converter‐based switched mode power supply (SMPS) for arc welding. By interleaving CSC converters, input current is shared amongst them so that high reliability and efficiency is obtained for high‐power applications. I‐CSC converter is designed to operate in discontinuous conduction mode (DCM) to achieve unity power factor inherently at utility interface. DCM operation together with interleaving technique bring additional size and performance benefits such as reduced reverse recovery loss, less switching stress, high efficiency, etc. I‐CSC converter is followed by three full bridge buck converters in parallel to perform DC‐DC conversion and to provide galvanic isolation desired for safe operation during welding. The modularity of SMPS allows flexibility in current, voltage and power levels, usage of devices of lower rating and ease of maintenance. The proposed SMPS operates in constant voltage mode; however, during extreme overload condition it maintains constant current at the output to improve the weld bead quality. Test results confirm the effectiveness of proposed SMPS in maintaining power quality indices within the acceptable limits of international standards over wide load range while over‐current handling capability leads to improved welding performance.